Perlindungan Hukum Terhadap Investor pada Investasi Illegal Secara Online dalam Perspektif Viktimologi - Kori Hermawanti; Intan Nuraini Sopiyanti; Hanifah Zakiyatun Nufus; Kuswandi Kuswandi (Universitas Serang Raya, 2022)
In general, Indonesians are still fairly unfamiliar with online investment, including online investment platforms and current rapid technological developments. This is the capital for perpetrators of illegal investment fraud online to commit their crimes. Often the illegal investment crime ends up being a case of fraud, even the victim's funds are difficult to return. This research is intended to find out about the statutory policies in handling criminal cases of illegal investment fraud online, and steps in suppressing cases of illegal investment fraud so as to create legal protection for investors. The method used in this study is normative juridical by combining various literature related to illegal online investment in Indonesia. Research shows that the legal protection of investors in illegal online investments has met the formulation contained in Articles 1 and 2 of the ITE Law. However, not all provisions stipulated in the ITE Law are related to online investment fraud. Only one clause in article 28 paragraph (1) contains acts as stipulated in article 378 of the Criminal Code on fraud. Although the elements in Article 378 of the Criminal Code are fully fulfilled, there is an element of online fraud. Until now, electronic media has not been known in the Criminal Code and the Criminal Code